Biosynthetic Precursors of Some Modified Nucleosides in the Transfer Ribonucleic Acid of Mycoplasma mycoides var. capri - Walker, R. T. (1971)
The ribosomal and transfer ribonucleic acid (tRNA) from Mycoplasma mycoides var. capri, grown in a medium containing uridine-((14)C)-5′-triphosphate and cytidine-(5-(3)H)-5′-triphosphate, were isolated and separated. The uridine in both species of RNA was shown to contain (14)C and the cytidine to contain both (3)H and (14)C. Comparison of the labeling of 4-thiouridine and pseudouridine, obtained from an enzymatic digest of the RNA, indicates that their biosynthetic precursor is uridine, not cytidine. It is probable that ribothymidine and dihydrouridine have the same derivation.